PROGRESS IN INTERNATIONAL READING LITERACY STUDY (PIRLS) - Aziza Amonova (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article reviews the achievements of the PIRLS international assessment program. The purpose, components of this program are mentioned. The procedure for conducting Reading Literacy, which is considered the main focus of the International Assessment Program is noted.